Pre-treatment subjective sleep quality as a predictive biomarker of tDCS effects in preclinical Alzheimer's disease patients: Secondary analysis of a randomised clinical trial. - Hanna Lu; Xi Ni; Sandra Sau Man Chan; Calvin Pak Wing Cheng; Waichi Chan; Linda Chiu Wa Lam (PLoS ONE)
Background Despite transcranial direct current stimulation (tDCS) has demonstrated encouraging potential for modulating the circadian rhythm, little is known about how well and sustainably tDCS might improve the subjective sleep quality in older adults. This study sought to determine how tDCS affected sleep quality and cognition, as well as how well pre-treatment sleep quality predicted tDCS effects on domain-specific cognitive functions in patients with mild neurocognitive disorder due to Alzheimer's disease (NCD-AD). Methods This clinical trial aimed to compare the effectiveness of tDCS and cognitive training in mild NCD-AD patients (n =  201). Over the course of four weeks, patients were randomized to receive either tDCS plus working memory training, or sham tDCS plus working memory training, or tDCS plus controlled cognitive training. The Pittsburgh Sleep Quality Index (PSQI) was used to measured subjective sleep quality. The Alzheimer's disease assessment scale-cognitive subscale (ADAS-Cog) was used to evaluate domain-specific cognitive functions. Results Recurrent tDCS treatments enhanced subjective sleep quality and cognition considerably. The poor sleepers (i.e., PSQI >  5) who received tDCS treatment had more cognitive benefits (p =  0.031, Cohen's d =  0.605) and sleep improvements (p <  0.001, Cohen's d =  1.209) in comparison to cognitive training. Pre-treatment subjective sleep quality was linked to tDCS-induced improvement in memory function. Conclusion During the course of two months, repeated tDCS could considerably enhance subjective sleep quality. For the cognitive benefits of the treatments, the status of pre-treatment subjective sleep quality is crucial. More thorough research is necessary to explore an efficient approach to managing comorbidities for preclinical AD patients.